Philanthropic zakat for the disadvantaged: Recipient perspectives from Indonesia. Issue 3 (20th July 2020) - Lessy, Zulkipli; Adamek, Margaret; Khaja, Khadija
Abstract: Rumah Zakat, a charitable institution, is a proactive provider of charity, enabling sustainable progress in the lives of needy recipients. This study focused on three forms of philanthropic zakat assistance: economic empowerment, health care, and tuition‐free education. There were 21 participants—seven from each respective cluster. Interviewers were employed to elicit participants' perspectives. Major findings showed economic empowerment recipients were the poor affected by the earthquake and the monetary crisis. Zakat helped them re‐open their businesses. As they grew, most felt satisfied and employed jobless individuals. Recipients of health care with elementary education had a five‐year grant of free health care and health education. Although the service lowered their expenses, some needed extra help with food. Participants benefitting from either program reported positive impacts on their income, health, and social lives. Most participants in the tuition‐free education were satisfied with their children's schooling, the extracurricular options, and the chances for parental involvement in the social engagement. Some stated the charitable schools emphasized moral education over science; thus, they were concerned about sufficient preparation for future competitive educational levels. Recipients would benefit from the charities if three programs were altogether offered. This study suggests the integrative community development programs should be reviewed for better services.